Effects of pre-exercise, endurance, and recovery designer sports drinks on performance during tennis tournament simulation - Peltier, S. L.; Lepretre, P.-M.; Metz, L.; Ennequin, G.; Aubineau, N.; Lescuyer, J. F.; Duclos, M.; Brink, T.; Sirvent, P. (The Journal of Strength and Conditioning Research, 2013)
Sports drinks are often used before, during, and after tennis tournaments, but their ability to influence physiological and psychological variables and the characteristics of tennis match play remains uncertain. The objective of this study was to evaluate the impact of ingesting specially formulated pre-exercise, endurance, and recovery sports drinks on glycemia and performance indices during a simulated tennis tournament. Eight well-trained male tennis players performed two 3-match round-robin tennis tournaments although ingesting sports drinks (SPDs) or placebos (PLAs) before, during, and after each match (crossover study design). Before the first tournament, match and drink order were randomized (SPDs or PLAs first) and players were placed under controlled nutritional and hydration conditions. Glycemia, heart rate response, rate of perceived exertion, and notational/match analysis were assessed during each match. Sports drinks maintained higher glycemia levels during match 2 and 3 of the tennis tournament compared with PLAs (p < 0.01). Moreover, higher mean heart rates (p < 0.01) and stroke frequencies (p < 0.01) concomitantly with lower rates of perceived exertion (p < 0.01) were recorded throughout the duration of the tournament, when players used the SPDs. During a 3-match tennis tournament, SPDs allow higher stroke frequency during play, with decreased rates of perceived exertion.